Binding Mode Prediction and Identification of New Lead Compounds from Natural Products as 3-OST Enzyme Inhibitors - Sousa, Rui; Moorthy, Narayana Subbiah H. N.; Fernandes, Pedro A.; Ramos, Maria Joao; Brás, Natércia Fernandes (Letters in Drug Design & Discovery, 2020)
Background and Introduction: The availability of antiviral medicines for the treatment of viral diseases is limited, hence the discovery of novel bioactive molecules is required. The present investigation has been carried out to develop novel 3-O-sulfotransferase enzyme inhibitors to treat viral diseases. Methods: Virtual screening study (QSAR, docking and pharmacophore analysis) and binding mode analysis have been performed on a dataset collected from the literature (synthetic and natural compounds). Results and Discussion: The docking studies showed that Glu184, His186, Lys215 and Lys368 residues established the most important hydrogen bonding with several hit compounds. The QSAR results explained that the presence of electronegative atoms/groups in the aromatic or heteroaromatic rings confer increased activity. Furthermore, the flexibility and the aromatic rings with less polar groups have better activity than the compounds connected to purine rings. Finally, the structurebased pharmacophore studies illustrated that the ligand has many polar interaction sites, and the projected acceptor and donor groups in the molecules make a significant contribution to the pharmacophore model building. Conclusion: These studies identified two compounds, Phomoidride B and Barceloneic acid A, as potential 3-OST inhibitors.
Keywords: heparan sulfate